Microsatellite evaluation of haddock ( Melanogrammus aeglefinus ) stocks in the northwest Atlantic Ocean - Lage, Christopher; Purcell, Maureen; Fogarty, Michael; Kornfield, Irv (Canadian Journal of Fisheries and Aquatic Sciences, 2001)
The goal of this study was to gain insight about the impact of intensive fishing on a single haddock (Melanogrammus aeglefinus) stock, and examine the genetic structuring of spatially discrete spawning aggregations in the northwest Atlantic. We analyzed genetic change at four microsatellite loci for Georges Bank haddock over a 40-year time span in which significant changes in demographics and abundances have occurred in the population. Allelic diversities have changed little, indicating that, although the commercial fishery has collapsed, stock sizes have remained large enough to insulate against major reductions in genetic variation due to drift. Results indicate significant genetic divergence among decadally separated samples. Potential causes for these differences include admixture from other spawning regions, fluctuations in the effective number of spawners contributing to a single spawning event, drift, or a combination of these. Examination of discrete spawning aggregations from Georges Bank, Browns Bank, the Scotian Shelf, and Nantucket Shoals indicated significant differences among stocks. Genetic distance based measures supported the clustering of Scotian Shelf, Browns Bank, and Georges Bank haddock to the exclusion of Nantucket Shoals haddock. Haddock spawning on Nantucket Shoals may be genetically discrete from other haddock populations in the northwest Atlantic.